Medical Clearance Prior to Psychiatric Evaluation in a Tertiary Pediatric Emergency Department: Value and Cost Analysis - Redfern, Roberta; Brown, Megan; Izsak, Eugene (Translation: The University of Toledo Journal of Medical Sciences, 2020)
Background: Medical clearance in the emergency department for patients undergoing psychiatric evaluation is often required prior to admission to rule out organic cause and because many psychiatric facilities are unable to treat medical conditions. This may be low yield in pediatric populations as the likelihood of disease requiring intervention is low in this setting. Objectives: To determine whether routine laboratory testing in an urban, tertiary pediatric hospital emergency center impacted the overall management of patients presenting with chief complaints requiring psychiatric evaluation. Methods: Retrospective analysis of all psychiatric admissions over a one year period at a large urban tertiary pediatric hospital. Laboratory test results were compared with history and physical notes to determine whether abnormal results could have been anticipated based on patient report. Additional medical interventions required and overall impact on management was recorded. Cost analysis was based on public reimbursement rates, considering tests without impact on intervention to be unnecessary. Results Overall, 1824 tests laboratory tests were performed in 289 patients admitted for psychiatric treatment. There were 161 abnormal results (8.8%), most of which could be anticipated by the medical history. No abnormal result laboratory result led to a change in management for any patient. The sensitivity and negative predictive value for patient-reported drug use compared to urine drug screen results were high, both over 90%. Conclusions Medical clearance in this population is low yield; most abnormal results can be anticipated by patient report or do not require any clinical intervention. The cost of these unnecessary tests was over 500,000.